2008
DOI: 10.1136/ard.2008.092775
|View full text |Cite
|
Sign up to set email alerts
|

Clinical subsequent fractures cluster in time after first fractures

Abstract: From menopause onwards, clinical fractures cluster in time, indicating the need for early action to prevent subsequent fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
125
2
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(146 citation statements)
references
References 15 publications
10
125
2
9
Order By: Relevance
“…This transient phenomenon will be missed in long-term follow-up studies where the pattern of risk with time is not studied [2,[19][20][21]. Several previous studies have found that a recent occurrence of fracture was a greater risk factor for subsequent fracture than a history of earlier fracture, demonstrated for vertebral fracture [6,11], hip, humeral and forearm fractures [3,6] and all fractures combined [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transient phenomenon will be missed in long-term follow-up studies where the pattern of risk with time is not studied [2,[19][20][21]. Several previous studies have found that a recent occurrence of fracture was a greater risk factor for subsequent fracture than a history of earlier fracture, demonstrated for vertebral fracture [6,11], hip, humeral and forearm fractures [3,6] and all fractures combined [12].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large meta-analysis showed that a prior fracture history was a significant risk factor for hip fracture at all ages but was highest at younger ages and decreased progressively with age [3]. Several studies have examined the time course of second fractures by site following an index fracture [6][7][8][9][10][11][12]. Fracture at the hip, forearm, spine or humerus (collectively termed major osteoporotic fractures) have been less frequently studied but (apart from rib fractures) comprise approximately 90% of the morbidity due to fracture [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Another shortcoming is that FRAX does not take into account the clustering of fractures in time, ie the risk of subsequent fractures after a first fracture is highest during the first years after a fracture, although the increased risk persists over longer time, be it at a lower level than immediately after a fracture. This has been documented for repeat vertebral, non-vertebral and all clinical fractures and recently also for repeat hip fractures van Geel et al 2009;Center et al 2007;van Helden et al 2006]. Ryg et al reported clustering of repeat hip fractures in a nation-wide registrar in Denmark including nearly 170,000 first and nearly 28,000 second hip fractures ( Figure 5) .…”
Section: Clinical Risk Factors For Hip Fracturementioning
confidence: 99%
“…The studies included by Klotzbuecher et al 149 in the meta-analysis had varying durations of follow-up, but generally > 1 year, so the estimates provided by Klotzbuecher et al 149 represent the RR when averaged over all years of study follow-up. The temporal profile of increased fracture risk after an incident fracture has been studied by van Geel et al 214 Their analysis suggests that the RR is approximately 2 when averaged over the long term, but when assessed over different time periods is much higher immediately after the first fracture, and tails off towards 1 over the next 20 years. We acknowledge that our method of applying a fixed RR over the patient's remaining lifetime probably underestimates the increased risk in the immediate years after fracture, but it is likely to overestimate the increased risk in the long term.…”
mentioning
confidence: 99%